Hemodynamics of cardiac tamponade during extracorporeal membrane oxygenation support in a patient with fulminant myocarditis. Issue 1 (January 2019) - Kondo, Toru; Morimoto, Ryota; Yokoi, Tsuyoshi; Yamaguchi, Shogo; Kuwayama, Tasuku; Haga, Tomoaki; Hiraiwa, Hiroaki; Sugiura, Yuki; Watanabe, Naoki; Kano, Naoaki; Ichii, Takeo; Fukaya, Kenji; et al.
Abstract: Fulminant myocarditis (FM) causes rapid onset severe heart failure requiring inotropes or mechanical circulatory support. Myocarditis is sometimes associated with pericardial effusion, however, how this effusion affects the hemodynamics in patients with FM under venoarterial extracorporeal membrane oxygenation (VA-ECMO) management has not been fully reported. We show a case of FM presenting with cardiac tamponade during VA-ECMO management. A 64-year-old female diagnosed as having FM showed a rapid hemodynamic collapse and that led to the application of VA-ECMO. Although her left ventricular ejection fraction did not improve despite proper hemodynamics management for several days, a pericardial effusion accumulated gradually. Apparent elevation of right atrial pressure and reduction of blood pressure were not observed, however, we performed pericardiocentesis because we were not able to wean off VA-ECMO. After the drainage of pericardial effusion, the blood pressure and cardiac output elevated as did the left ventricular ejection fraction. We successfully removed VA-ECMO and the patient was discharged without any complications. This is a case report in which a cardiac tamponade under VA-ECMO did not show typical signs and pericardiocentesis contributed to withdrawal of a VA-ECMO system. <Learning objective: Typical findings of cardiac tamponade are less likely to appear in patients with fulminant myocarditis under venoarterial extracorporeal membrane oxygenation management (VA-ECMO). Drainage of pericardial effusion delivers dramatic improvement in blood pressure, cardiac output, and left ventricular ejection fraction. When VA-ECMO cannot be weaned off, pericardiocentesis should be considered in patients with fulminant myocarditis who showed gradual accumulation of pericardial effusion.>